![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có :\(\frac{1}{x}=\frac{1}{2}\left(\frac{1}{y}+\frac{1}{z}\right)\)
=> \(\frac{1}{x}=\frac{y+z}{2yz}\)
=> 2yz = x(y + z)
=> 2yz - xy - xz = 0
=> (yz - xy) + (yz - xz) = 0
=> y(z - x) + z(y- x) = 0
=> y(z - x) = -z(y - x)
=> -y(x - z) = -z(y - x)
=> \(\frac{-z}{-y}=\frac{x-z}{y-x}\Leftrightarrow\frac{z}{y}=\frac{x-z}{y-x}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\dfrac{1}{x}-\dfrac{1}{y}=\dfrac{1}{x}.\dfrac{1}{y}\)
\(\Rightarrow\dfrac{y-x}{xy}=\dfrac{1}{xy}\)
\(\Rightarrow y-x=1\)
\(\Rightarrow y=x+1\)
Vậy S={x,y∈N*\(|y=x+1\)}
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Đề sai rồi phãi là: \(A= ( 1-\frac{z}{x})(1-\frac{x}{y})(1-\frac{y}{z}) \)
\(A=\left(\frac{x-z}{x}\right)\left(\frac{y-x}{y}\right)\left(\frac{z-y}{z}\right)\)
Từ x-y-z = 0 \(\Rightarrow\) x-z = y
y-x = z
z-y = x
Thay vào A, ta có: \(\left(\frac{y}{x}\right)\left(\frac{z}{y}\right)\left(\frac{x}{z}\right)\)
\(\Rightarrow A = 1 \)